2017
DOI: 10.1016/j.polymer.2017.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Ionic complexes of poly(γ-glutamic acid) with alkyltrimethylphosphonium surfactants

Abstract: A series of ionic complexes with a comb-like architecture and a nearly stoichiometric composition were prepared from bacterial poly(DL-glutamic acid) (PGGA) and alkyltrimethyl phosphonium bromides (nATMP·Br) bearing long linear alkyl chains with even numbers of carbon atoms (n) ranging from 12 to 22. The nATMP·PGGA complexes were non-water soluble but readily soluble in organic solvents, and they displayed a high thermal stability. Combined DSC and XRD studies revealed that these complexes adopted an amphiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The TGA traces recorded for the two nanocomposite series ( n = 12 and 20), including the two P MMT modified clays ( X = 100%) as well as the two n ATMP·PGGA complexes ( X = 0%), are compared in Figure , and the more relevant thermal decomposition parameters afforded by this analysis are listed in Table 1 . TGA results indicated that decomposition of these nanocomposites induced by heating was found to proceed along two steps following a pattern similar to that displayed by the n ATMP·PGGA complexes …”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…The TGA traces recorded for the two nanocomposite series ( n = 12 and 20), including the two P MMT modified clays ( X = 100%) as well as the two n ATMP·PGGA complexes ( X = 0%), are compared in Figure , and the more relevant thermal decomposition parameters afforded by this analysis are listed in Table 1 . TGA results indicated that decomposition of these nanocomposites induced by heating was found to proceed along two steps following a pattern similar to that displayed by the n ATMP·PGGA complexes …”
Section: Resultsmentioning
confidence: 72%
“…The thermal behavior of nanocomposites regarding melting‐crystallization was examined by differential scanning calorimetry (DSC). It is known that n ATMP·PGGA complexes display crystallinity only for n = 16, 18, 20, and 22, which is associated to the ordered close packing adopted by the polymethylene chains . Accordingly, the DSC analysis of 12ATMP·PGGA· X % P MMT nanocomposites did not show melting for whichever composition due to the inability of dodecyl chains to crystallize.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations